Gradually decreasing daylength after smoltification induced by “winter signal“ reduced sexual maturation in male Atlantic salmon - Skjold, Vetle; Rørvik, Kjell-Arne; Sveen, Lene; Burgerhout, Erik; Mota, Vasco C.; Weihe, Rúni; Ytrestøyl, Trine; Bou, Marta; Jacobsen, Hans Jákup; Allaoui, Giovanni; Fuskevåg, Ole-Martin; Dessen, Jens-Erik (Frontiers in Aquaculture, 2024)
Introduction Maturation in seawater-adapted (smoltified) male Atlantic salmon is undesirable yet frequently reported in fish weighing up to 1 kg reared under intensive conditions in land-based facilities. Although the photoperiod regulates both smoltification and maturation, the optimal post-smoltification regimen for the prevention of maturation is unclear. Methods In this study, mixed-sex Atlantic salmon weighing 95 g were exposed to three different photoperiod regimes: continuous daylength, gradually decreasing daylength, and short-to-long daylength after the induction of smoltification by the “winter signal” (12 h:12 h light:dark). Fish were maintained under these conditions in triplicate for 18 weeks in a brackish water flow-through system at 12°C and with a salinity of 20 ppt. This initial phase was followed by a grow-out period (1 kg–2.5 kg) in seawater (32-ppt salinity) at 13°C for 11 weeks, with exposure to decreasing daylength. Throughout the 29-week study, body condition, gonad development, and morphological traits were assessed. Additionally, during exposure to brackish water, serum 11-ketotestosterone (11-KT) levels were quantified, and the testes were examined histologically. Upon termination of the study, the maturation rate was determined. Results This study exclusively detected maturation among male salmon. Under continuous light exposure, the number of fish initiating maturity steadily increased from week 8 and continued to increase in the subsequent samplings. In the short-to-long daylength group, a subset of male fish showed elevated 11-KT levels at week 14, although their gonadal development and morphological changes were not evident until week 18. Male fish exposed to decreasing daylength showed no substantial increase in 11-KT levels, although a few fish exhibited advanced gonad development by week 18. At the end of the trial, markedly lower percentages of maturing and fully mature male fish were observed among those fish previously exposed to decreasing daylength. The maturation rates at study termination were 44.4% for the short-to-long daylength group, 29.4% for the continuous daylength group, and 4.3% for the decreasing daylength group. Discussion These results show that photoperiod can be utilized to regulate maturation in male Atlantic salmon. In addition, decreasing the photoperiod after smoltification seems to limit early sexual maturation without compromising body size development. Thus, decreasing the photoperiod could be utilized to limit maturation in the production of post-smolt salmon or salmon in land-based facilities.